2021
DOI: 10.1097/md.0000000000025250
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion therapy for treating psoriasis vulgaris

Abstract: Background: Psoriasis vulgaris (PV) is an immune-mediated skin disease, which has seriously affected the quality of life of patients. At present, moxibustion therapy has been widely used in the treatment of PV. The purpose of this study is to provide high-quality evidence-based medicine to evaluate the effectiveness and safety of moxibustion for PV. Methods: We will search the following Electronic databases from their inceptions to February 2021 without any language lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A variety of tests have determined that the response is either all-encompassing, restricted to the nails exclusively, or a hybrid of the two. Pitches are the small, sharp depressions on the nail's surface are the most common and immediately obvious symptom of a problem [ 7 ]. There are no differences in terms of size or depth between everything ( Table 2 ).…”
Section: Types Of Psoriasismentioning
confidence: 99%
“…A variety of tests have determined that the response is either all-encompassing, restricted to the nails exclusively, or a hybrid of the two. Pitches are the small, sharp depressions on the nail's surface are the most common and immediately obvious symptom of a problem [ 7 ]. There are no differences in terms of size or depth between everything ( Table 2 ).…”
Section: Types Of Psoriasismentioning
confidence: 99%
“…Studies showed that needling can improve venous circulation which is suggested by pelvic magnetic resonance venography imaging [ 59 ]. Moxibustion features high safety and low cost and so on including moxibustion on governor vessel acupoints, cotton moxibustion, medicinal thread moxibustion and pyretic moxibustion and the such [ 60 ]. Studies concerning moxibustion in the treatment of chronic CP/CPPS are relative less nowadays which indicated that the primary mechanism of moxibustion in the treatment of CP/CPPS is to improve whole blood reduced viscosity, white blood cell rigidity index, aggregation index and the level of fibrinogen to ameliorate hemorheology state by exerting thermal stimulation on blood vessel and tissues [ 28 , 61 ].…”
Section: Discussionmentioning
confidence: 99%